Специфіка навчальної мотивації дітей сільських шкіл - Мищишин, Марія; Кравчук, Олена (Видавництво Львівської політехніки, 2013)
The work deals with psychological and pedagogical phenomena of learning motivation and its importance in rural school. The main differences in the formation of learning motivation of children in rural and urban schools are defined. For this purpose, the impact of socio-cultural environment and living conditions on the formation of the individual student is determined and its fundamental role in the formation of learning motivation is considered. The motivational sphere of the students is analyzed. There is represented the pilot study of learning motivation among the students of Lviv Polytechnic National University. The prospects of further studies on this subject are revealed.
Keywords: motive; motivation; socio-cultural environment; needs; goals; motivational sphere